Four new species of Splendid Ghost Moths (Lepidoptera: Hepialidae: Aenetus) from Australia and Papua New Guinea - Beaver, Ethan P.; Moore, Michael D.; Grehan, John R.; Velasco-Castrillón, Alejandro; Stevens, Mark I. (Zootaxa, 2020)
Four new Aenetus Herrich-Schäffer species are described from northern Australasia; Aenetus simonseni sp. nov. from the top-end of the Northern Territory, Australia, A. maiasinus sp. nov. from the Kimberley region of Western Australia, A. trigonogrammus sp. nov. from south-eastern Queensland, Australia, and A. albadamanteum sp. nov. from eastern Papua New Guinea. Aenetus simonseni sp. nov. and A. maiasinus sp. nov. appear to belong to the tegulatus-group of species (sensu Grehan et al. 2018), A. trigonogrammus sp. nov. is part of the splendens-group of species (sensu Simonsen 2018), while A. albadamanteum sp. nov. shares morphological similarities with A. hampsoni (Joicey & Noakes, 1914), A. crameri Viette, 1956, and A. toxopeusi Viette, 1956, from New Guinea, and A. cohici Viette, 1961 from New Caledonia. The four new species are illustrated and compared with superficially similar species in morphology and, for two species, molecular (mtDNA COI gene) sequences.